AC - DC power supply / Mohd Fahmi Abdul Halim and Mohd Fadlie Chan Mahadie Chan - Abdul Halim, Mohd Fahmi; Mahadie Chan, Mohd Fadlie Chan (2005)
Nowadays, AC to DC power supply is very important in our lifestyle and used widely in many commercial sectors especially in industrial, laboratory and public consumer. We also used the AC-DC power supply everyday. Hand phone charger and notebook some of application of AC-DC power supply. Power supply introduces the operation of power supply circuits that consists of transformer, filters, rectifiers and voltage regulator. In our project, we decrease the voltage using step-down transformer. After that, a steady dc voltage is obtained by rectifying the ac voltage using the full wave bridge rectifier. The process also known as pulsating dc. In other words, it converts the ac signal to a dc signal which is unidirectional waveform (full wave waveform). Then, we filter the dc voltage to a dc level using the simple capacitor. This resulting dc voltage usually has some ripple or ac voltage variation. Finally, the dc voltage is regulated to obtain a desired fixed dc voltage. The regulation is usually obtained from an integrated circuit (IC) voltage regulator unit, which takes a dc voltage and provides somewhat lower dc voltages which remain the same even if the input dc voltage varies or the output load connected to the dc voltage changes. In other words, a voltage regulator is used to maintain a constant output voltage. The significant advantages of this project are almost all application of electronics devices used dc voltage. For example, Walkman, radio, torchlight etc.